The Effectiveness of Case Resolution with E-Court during the Covid-19 Period at the Probolinggo Religious Court - Putri Qurratul Aini; Fathullah Rusly; Irzak Yuliardy Nugroho (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2023)
This article discusses the Effectiveness of E-Court Case Resolution during the Covid-19 Period at the Probolinggo Religious Court. The sub-topic of discussion or the formulation of the problem here is how to implement the settlement of cases with the e-court system during the Covid-19 pandemic at the Probolinggo City Religious Court, the effectiveness of the E-Court system during the Covid-19 pandemic and what are the Obstacles and Challenges for E-System Services Court for the people of Probolinggo City at the Religious Court of Probolinggo City. This research was carried out at the Religious Court of Probolinggo City using a normative juridical research type by researching and examining theories, concepts, legal principles and related laws and regulations. Data acquisition is taken from primary and secondary data. The data acquisition method is by interviewing and taking data related to research. However, there are still many Probolinggo City residents who are in litigation who do not know about the existence of an E-court system due to the lack of socialization from the courts and because of several factors such as people who are technologically illiterate. It is better for the government that the e-court system can be socialized more clearly to the people who are in litigation and wish to register their case status through the e-court.